The Rise and Recent Decline of Tesla’s Share of the U.S. Electric Vehicle Market - Chang (Charo) Liu; Stella G. Boothman; John D. Graham (World Electric Vehicle Journal, 2025)
This article examines the rise and recent decline of Tesla in the U.S. electric vehicle market. Using qualitative, semi-quantitative, and statistical methods, the article traces how Tesla acquired a first-mover advantage and how second movers, both established automakers and start-ups, responded to Tesla’s rise. The recent decline in Tesla’s share of the U.S. electric vehicle market is linked to several factors: the proliferation of electric vehicle offerings from competitors, changes in public policy, and controversial decisions by Tesla and its CEO. The article concludes with a discussion of promising future strategies for both Tesla and its competitors.